Pengaruh E-Procurement, Kualitas Produk Terhadap Keputusan Pembelian Dimoderasi Oleh Pelayanan Purna Jual Studi Pada Produk Smartkey & Smartlock Di Pt Netwave Maju Abadi. - Pristiana Widyastuti; Mochammad Angga Prasetyo (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
This study aims to examine the effect of e-procurement, product quality on purchasing decisions moderated by after-sales service, studies on smartkey and smartlock products at PT Netwave Maju Abadi. The unit of analysis in this study is the customer of PT Netwave Maju Abadi. The population in this study were customers who purchased the product and purchased the smartkey and smartlock at PT Netwave Maju Abadi with a sample of 60 respondents. The sampling method in this study uses a Purposive sampling technique with special characteristics in accordance with the research objectives. The type of data used is primary data using a questionnaire which is filled directly by the respondent and then processes the data using Partial Least Square (PLS). The statistical results of the research data show (X1) e-procurement has no significant effect on purchasing decisions, whereas (X2) product quality, (Z) after-sales service has a positive and significant effect on (Y) purchasing decisions, while service moderation after-sales of e-procurement and product quality have no significant effect.Keywords : E-Procurement, Product Quality, Purchase Decision, After Sales Service.